Disentangling inhibition and prediction in negation processing - Haase, Viviana (Frontiers in Language Sciences, 2024)
Negation as a universal feature of human language is used effortlessly in everyday communication. However, experimental research has shown that the comprehension of negated sentences seems to require additional cognitive resources compared to affirmative sentences. Many studies investigating the processing of negation report longer reading and reaction times for negative compared to affirmative sentences and many studies report a Polarity by Truth interaction: false affirmative sentences lead to longer response times and larger N400 event-related potentials (ERPs) than true affirmative sentences, whereas the pattern is reversed for negative sentences where it is the true sentence that elicits longer reaction times and higher N400 ERPs compared to false negative sentences. These interactions have been discussed in the light of lexical associations, predictability, and the need to construct two subsequent mental representations.Furthermore, recent studies have shown that the comprehension of negated sentences seems to make use of neural resources that are typically involved in cognitive control and inhibitory mechanisms. This article reviews results on the prediction and inhibition in language comprehension with a focus on negated sentences. As both processes have been associated with two different and temporally overlapping ERP components (the N400 and the P300), we focus on studies with high temporal resolution. We discuss linguistic aspects of negation, such as semantic similarity and contextual invariance of negation. We furthermore discuss the role of the verb as well as the position of the negative marker with respect to the verb, and their respective relevance for predictive and inhibitory mechanisms in negated sentences.